The Vilnius Region Battalions of the Lithuanian Self-Defence Subunits (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2008)
The Vilnius region Lithuanian battalions were formed between July and September 1941 from Lithuanian troops of the 29th Territorial Riflemen’s Corps of the Red Army, who were taken prisoners of war. Before October that year six police battalions were formed in the Vilnius region: the First, Second, Third, Fourth battalions and the Railway Guard Battalion (which later got No 6) and the Gardinas Battalion (later under No 15). In these battalions and other self-defence subunits 3,000 troops served then. In the spring 1942, the 254th Police Battalion was formed in the Vilnius region. The police battalions, which served in Vilnius, most often guarded various military objects (warehouses, railway bridges, bridges, barracks etc.). Almost all battalions formed in Vilnius in 1941 (except the Railway Guard Battalion and the Gardinas Battalion) got involved in the Holocaust in the autumn that year (they participated in moving Jews from their homes to the ghetto, served as ghetto guards, convoyed the Jews who were driven from Lukiškės prison to Paneriai to be exterminated, stood guard during mass executions). The First Vilnius Battalion also took part in the massacre of Jews in Paneriai on 5 April 1943, and the liquidation of the Vilnius ghetto labour camps (in Bezdonys, Kena) in the summer 1943.At the end of 1941 and the first half of 1942 almost all Vilnius region battalions (except the First and the Railway Guard battalions) were sent from Lithuania: the Third and No 254 were deployed in Belarus and the Forth in Ukraine (the Second battalion was sent to Poland to guard Maidanek concentration camp). There they were tasked with guarding military objects (railways, roads, bridges, PoW camps) as well as fighting Soviet partisans. In Belarus, the Lithuanian battalions together with German, Latvian and other subunits took part in burning villages and shooting civilians who supported Soviet partisans. Due to the lack of reliable sources it is impossible to establish an exact figure of the villages burnt, Soviet partisans and the local civilians killed by the Lithuanian battalions. It is possible to suppose that the Vilnius region battalions killed several scores of partisans and their supporters. The Third Battalion, which fought in Belarus for almost three years, led the most intensive fight against the partisans. It also sustained the greatest losses. Several scores of the battalion’s troops were killed and injured in the fights against the partisans. The losses of other battalions were smaller. It can be supposed that the total number of the Vilnius region battalion troops killed did not exceed a hundred. Some losses were due to the fact that some troops were taken PoWs and deserted. Desertion was characteristic of all battalions and was on the increase in 1943 and 1944. During the time when the Vilnius region battalions were in operation several hundreds of troops deserted. The number of the battalions’ troops (except the Forth Battalion) who were taken prisoners by the Soviet army and partisans was smaller. All the Vilnius region battalions ceased to exist before the autumn of 1944. Most of them were disbanded in the East Prussia (in Tilžė) in the summer of 1944. Most of the Lithuanian troops were sent to various German air defence subunits. At the end of war they were taken prisoners by the Soviets or the allied forces.
Keywords: German occupation; collaborants; Holocaust; Vilnius; police battalions